PENGUNGKAPAN SEKSUALITAS DALAM SENI SASTRA: METAFOR SEKSUAL - Yeni Mulyani Supriatin (Jurnal Sosioteknologi, 2011)
This paper presents various literary works, both novels and poems that contain sexuality. The disclosure of sexuality in literature are generally conveyed through metaphor. The disclosure of sexuality in literature through the metaphor in this paper will be highlighted by using the concept developed by Lackoff adopted by Danesi and Perron (via Cristommy) in cultural semiotics. The purpose of this study is to have the depiction of sexuality in the literature works not done vulgarly, but uses a unique metaphor. The results showed that the presence of the sexual metaphor depiction of sexuality does not cause impression of pornography. Keywords: sexual metaphor, pornography, and cultural semiotics